Linking Financial Service Providers to Commercial Capital : How Do Guarantees Add Value? - Latortue, Alexia; Glisovic-Mezieres, Jasmina (World Bank, Washington, DC, 2012)
In microfinance, experimentation with loan guarantees began largely as an attempt to demonstrate to local banks that Microfinance Institutions (MFIs) are creditworthy. Though loan guarantees are far less common than other funding instruments, such as debt, equity, and grants, they are beginning to be used more often. This brief is based on a joint Consultative Group to Assist the Poorest (CGAP)/United States Agency for International Development (USAID) study of 96 transactions executed by eight guarantor agencies between 1988 and 2005, with most transactions made after 2000.